Morality in Higher Education's AI Integration: Examining Ethical Stances on Implementation - Zohaib Hasan Sain; Usman Shihu Laval (Indonesian Journal of Education and Social Studies, 2023)
The research focuses on transparency and education related to artificial intelligence (AI) in higher education, as well as how these two factors affect the acceptance of technology by students and academic staff. The main objective of this study is to explore users' views and attitudes towards the use of AI, with a special emphasis on ethical and practical aspects. This study uses a mixed approach, combining quantitative surveys and qualitative interviews conducted at Superior University, Lahore, Pakistan. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed by thematic methods. The results of the study showed that 75.2% of respondents supported education and transparency related to AI. A total of 54.7% of respondents expressed concern that AI could threaten academic integrity if it is not used transparently and fairly. However, 45.3% of respondents see AI as an effective tool to detect plagiarism and improve academic supervision. The implications of this study underscore the importance of comprehensive education and transparency policies to ensure the ethical and effective use of AI in higher education. This research provides an empirical foundation for the development of policies that can increase trust and acceptance of AI in academic contexts.